Metode Riyadhotun Nafs Menuju Mardhatilah Dalam Perspektif Para Sufah - Julaeha, Siti; Muslim, Erwin; Ahmad, Nurwadjah; Suhartini, Andewi (Al-Wasathiyah: Journal of Islamic Studies, 2022)
Happiness is the hope and dream of every human being as the ultimate goal of everything, happiness and safety are the ideals in every life. But where can we find happiness? Some people argue that the source of happiness is abundant wealth, high positions, or a lot of knowledge so that mistakes in perspective make the human paradigm deviate from achieving life goals. For people who believe, they will know that the true source of happiness lies not in abundant wealth, high positions, or a lot of knowledge, but lies in the pleasure of Allah SWT. Therefore, the ultimate goal of a believer is to reach the pleasure of Allah SWT (mardhotillah), in achieving it to get mardhotollah is not as easy as turning the palm of the hand riyadhotun nafs method is one method in achieving mardhotillah, stages and lifestyles that are carried out consistently doing riyadhoh In Sufism it is called maqomat, while maqomat is the inner level in doing soul training towards the kholiq, Dusi expression (2015: 196)